Religião & negócio: religiosidade como fator estruturante do novo espírito do capitalismo - Silva, Maroni João da (2017)
This Project investigates the role played by belief and faith in the corporate culture of three major retail companies in Brazil, where they seem to contribute to stimulate employees to engage on their business strategies. The objective is to unveil the meaning of these categories in the training rituals at Magazine Luiza, voluntary works done by Carrefour employees, and enchantment of clients at Lojas Renner. My thesis advocates that by means of these three entrance doors of religiosity, the companies develop a favorable ethics in order to create a new spirit of commercial capitalism, based on Weber (2007) theory and revisited by Boltanki and Chiapello (2009). A series of flows of images, values, symbols and meanings, including those of a religious nature, which correspond to new cultural dimensions of globalization, have facilitated new institutional arrangements through which the capitalism reinvented itself in those companies. In this respect, the similarities among studies on self-help, prosperity theology and Christian practices are discussed in order to help in the analysis of the function of religiosity as a structuring factor of a “power of the mind”. Apparently, this ethos acts like an ideology according to which prosperity and social well-being are two sides of the same coin, i.e. profit. Authors like Appadurai (2006), Balandier (1999), Boltanski and Chiapello (2009), Bourdieu (2005), Geertz (1989), Weber (2004), and Simmel (2010), among others, will be structural references for analyses. The corresponding data have been obtained by means of a multimethod strategy based on three case studies. I have specifically investigated rituals at Magazine Luiza and interviewed employees and managers, gathered data from documents, including presentations, papers, manuals, and videos at the company’s websites. I also have gotten some references in magazine and newspapers’ reports, theses and articles